A rare case of an Omphalocele Major with associated Tetralogy of Fallot in a newborn - Shah, Dharmendra K.; Chaudhary, Shivani R.; Shah, Margi A. (International Journal of Contemporary Pediatrics, 2022)
Omphalocele major (OM) is a surgically challenging condition which owing to its large defect size and other congenital anomalies, is associated with poor outcomes. Complications while managing it are not uncommon. But here, we report a case of OM in a neonate who was successfully managed in a multidisciplinary approach by a team of neonatologist, surgeons and anesthetist.